Intensive Care and Death with Dignity: Ethical, Clinical and Regulatory Aspects at the End of Life - Guzmán, Camila (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Intensive care units (ICUs) were designed to care for critically ill patients who require continuous monitoring and specialized care. These units use advanced technology, such as mechanical ventilation and hemodialysis, to sustain vital functions. However, prolonging life in critical situations raises ethical dilemmas, especially in cases of terminal or brain-dead patients. The implementation of disproportionate measures may prevent a dignified death, diverting natural death. In this context, the right to a dignified death, regulated in countries such as Argentina by Law No. 26742, which protects patient autonomy in the final stage of life, was discussed.Development: Studies analyzed the application of regulations on dignified death and palliative care in different contexts. The results indicated that many professionals were unaware of key aspects of the legislation, although they respected basic ethical principles. Protocols for diagnosing brain death were based on rigorous clinical criteria and confirmatory techniques such as electroencephalogram. However, barriers to ensuring a dignified death included the lack of training in ethical and cultural aspects, the absence of updated protocols, and difficulties in communicating with family members. These factors limited the effective implementation of advance directives and informed consent.Conclusions: ICU care and end-of-life management required a combination of technical expertise and ethical sensitivity. Continuing education of healthcare personnel, development of clear protocols, and promotion of a humanized approach were essential to respect patient dignity and autonomy, providing adequate palliative care and allowing informed decisions in terminal situations.